The influence of iron (Fe) Content Elements on Mechanical Properties of Aluminum-Silicon Alloy Wheels A356 for Car Rims - Aditya, Geraldi Raka (Mechanova, 2017)
Aluminum-silicon alloy A356 is material for the manufacture of rims. Rims are important components for the vehicle, so it must be strong enough to withstand the vertical load, the side load and the braking force. In the process of casting in car rims factories usually occurs error, such as the inclusion of the bolts that will lead to increased content of Fe. High level of Fe can lower the toughness and the ductility properties. This study aims to get the value of the mechanical properties (impact strength and tensile strength) of Al-Si alloy A356 as the effect of variations in the levels of Fe (0.12 wt%; 0.16% by weight; 0.20% by weight) and to study the relationship between the microstructure and the mechanical properties.From the experiments, it is known that increased levels of Fe cause a decline in the value of elongation, yield strength and ultimate tensile strength. In addition, with the increase of Fe content obtained, impact values also fell. This occurs due to the presence of porosity in the casting result which causes the wheels become brittle. In addition, the decreasing value of UTS is due to enlargement of the grain size and the size of the dendrites observed through the test micro-structure.